EU-7 zeolite: a synthetic BIK type zeolite with high hydrothermal stability. Issue 44 (17th May 2018) - De Prins, Michiel; Verheyen, Elke; Kerkhofs, Stef; Hoffmann, Andreas; Vanbutsele, Gina; Sree, Sreeprasanth Pulinthanathu; Radhakrishnan, Sambhu; Van Tendeloo, Leen; Breynaert, Eric; Kirschhock, Christine E. A.; Schütze, Frank-Walter; Martens, Johan A.
Abstract : EU-7 is identified as BIK topology and proves stable to withstand steaming at 900 °C relevant to DeNOx catalysis. Abstract : EU-7 zeolite with Si/Al ratio of 15 is identified as a BIK type zeolite. The framework charge is compensated with Cs + cations located in 8-ring channels at regular distances. Even partially exchanged, Cu-loaded EU-7 is active in NH3 -SCR and withstands hydrothermal aging at 900 °C needed for application in diesel particulate filters.